How does portfolio assess interprofessional learning of medical and midwifery students in community-based maternal and children health care - Bulan Kakanita Hermasari; Gandes Retno Rahayu; Mora Claramita (International Journal of Evaluation and Research in Education (IJERE), 2019)
Top-quality maternal health care requires midwifery and medical students to work together in multidisciplinary interprofessional education (IPE). Achieving IPE learning competencies requires interprofessional assessment methods; one such is portfolio. Study on portfolio as interprofessional assessment is limited. To evaluate interprofessional core competencies illustrated by IPE portfolios. A qualitative design using content analysis to evaluate portfolios of midwifery and medical students attending three weeks’ interprofessional learning in an Indonesian university. Sixty portfolios were analyzed for four IPE core competencies. Fifteen open-ended questionnaires were collected to confirm the data and further explore issues. Four interprofessional core competencies were illustrated in portfolios. While only three portfolios contained objective evidence of learning, over two-thirds of students could plan appropriate, concrete work based on interprofessional learning. The results indicate that the portfolio assesses interprofessional learning with student reflections that illustrate the achievement of four IPE core competencies. The validity of this competency achievement is also supported and confirmed by the evidence of learning and subsequent learning plans. Furthermore, portfolios also can encourage the students to prepare a concrete and appropriate work plan or study plan for students’ interprofessional learning.